Perilaku Remaja Pengguna Gadget: Studi dan Analisis pada Teori Sosiologi Pendidikan - Nur Hidayah (ANWARUL, 2025)
The limited number of studies examining adolescent gadget use from the perspective of educational sociology serves as the background for this research, despite the phenomenon’s significant influence on the processes of socialization, identity formation, and patterns of social interaction among youth in the digital era. The primary objective of this study is to explore the sociological factors influencing adolescents’ gadget use and to identify forms of social deviance arising from excessive usage. A qualitative approach was employed, using purposive sampling to involve 20 adolescents, 5 parents, and 5 teachers. Data were collected through semi-structured interviews, observation, and documentation, and analyzed thematically. The findings reveal that intensive gadget use negatively impacts adolescents’ psychosocial development, including tendencies toward introversion, reduced engagement in real-life social interactions, and the emergence of deviant behaviors. These results support symbolic interactionism and social learning theory within the framework of educational sociology. The study concludes that active involvement from both families and schools is crucial in guiding adolescents to use technology wisely. The implications of this research include theoretical contributions to the enrichment of educational sociology literature and practical recommendations for governments, schools, and parents to enhance digital literacy and develop healthy gadget use policies.